Staking out the successful student - Brown, Christopher (Education Policy Analysis Archives, 2005)
With the performance of students, teachers, and schools defining success under current standards-based accountability policies (e.g. Chicago Public Schools (Note 1); No Child Left Behind Act, (United States Department of Education, 2002)), school districts are implementing various forms of intervention programs as a means to improve student performance. By examining a pilot summer school program that is transitioning from a low-stakes' to a high-stakes' intervention program, this article examines the possibilities that exist for students to author themselves as learners, and it questions whether opportunities for students to identify themselves as successful learners are lost when an intervention program, such as summer school, becomes mandatory. The implications of this analysis highlight questions and concerns that policymakers and school personnel need to address when formulating high-stakes standards-based accountability policies and intervention programs.